Purchasing and Supply Chain Management, 7th Edition - Robert Monczka (Cengage Learning, 2020)
Gain a thorough understanding of today's supply management process from a managerial perspective with the current, complete coverage found in Monczka/Handfield/Giunipero/Patterson's PURCHASING AND SUPPLY CHAIN MANAGEMENT, 7E. This edition draws from the authors' extensive first-hand experiences and relationships with executives and practitioners worldwide to highlight critical developments in the field. You examine recent advancements in supply chain fraud management, artificial intelligence, analytics, procurement automation and robotic process automation. New content also discusses supply chain fraud management and mitigation, emerging technology in real-time supply chain control towers, use of blockchain and the creation of Centers of Excellence. The authors carefully select topics that correspond to hiring requirements for supply chain positions today. Position yourself to step into a role in procurement and supply management as you master the strategies, processes and practice in this edition. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.